Andeepia ingridae a new genus and species of Pardaliscidae (Crustacea, Amphipoda) from the Antarctic deep-sea and short redescription of Nicippe unidentata K.H. Barnard, 1932 - Biswas, Tapati; Coleman, Charles Oliver; Hendrycks, Ed A. (Zootaxa, 2009)
The new genus and species Andeepia ingridae is described. The main features of this taxon are: urosomite 2 with middorsal tooth; massive propodi of gnathopods 1–2; carpus of gnathopod 1 short, weakly lobate and half the length of that of gnathopod 2; dactylus of gnathopod 2 with distinct dentition on the inner margin; dactylus of gnathopod 1 smooth, lacking dentition, but in the cuticle with faint trace of embedded teeth and reduced setation on pereopods and uropods. The related southern ocean pardaliscid, Nicippe unidentata K.H. Barnard, 1932 is also re-described and illustrated for the first time from the type material.